2010
DOI: 10.3109/09553002.2010.518211
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear magnetic resonance spectroscopy-based metabonomic investigation of biochemical effects in serum of γ-irradiated mice

Abstract: The information obtained from this study reflects multiple physiological dysfunctions. The study promises the application of NMR-based metabonomics in the field of radiobiology, for development of metabolic-based markers for screening of risk populations and medical management in these cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 27 publications
4
37
1
Order By: Relevance
“…These and other energy metabolites represent bioenergetic status of the body and might have resulted from increased energy demands and were, therefore, suggestive of changes in energy metabolism after radiation exposure (Lerman et al 1962). Dose dependent acute effects of radiation showing altered membrane and energy metabolism in serum have been reported in our earlier study (Khan et al 2010). In this study, highest increase in the energy intermediates was observed at 6 h post dose in urine samples.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…These and other energy metabolites represent bioenergetic status of the body and might have resulted from increased energy demands and were, therefore, suggestive of changes in energy metabolism after radiation exposure (Lerman et al 1962). Dose dependent acute effects of radiation showing altered membrane and energy metabolism in serum have been reported in our earlier study (Khan et al 2010). In this study, highest increase in the energy intermediates was observed at 6 h post dose in urine samples.…”
Section: Resultssupporting
confidence: 58%
“…Serum and urine samples provide a well established surrogate medium for the study of metabolic physiological functions of not only liver and kidney, but also for other vital organs. Earlier studies in the field of radiation metabolomics have shown time and dose dependent changes due to acute radiation stress in animal model and cell system (Tyburski et al 2008;Lanz et al 2009;Patterson et al 2009;Wang et al 2009;Khan et al 2010). However, metabolic changes during different phases of radiation sickness are yet to be elucidated.…”
Section: Introductionmentioning
confidence: 96%
“…Possible explanations for shifts in amino acid serum concentrations have been protein breakdown, altered amino acid metabolism, diet shifts, cell death, and damage to kidneys and intestinal lining. 10,17,19,22,32 …”
Section: Discussionmentioning
confidence: 99%
“…Within the field of radiation metabolomics, past studies have primarily utilized liquid chromatography (LC) mass spectrometry (MS), 5,8,11,1318 with less attention given to gas chromatography (GC) MS 7,1921 and nuclear magnetic resonance (NMR) platforms. 22 GC–MS is a well-established bioanalytical platform ideal for detecting myriad molecules including volatile small metabolites, isomeric compounds, derivatized organic acids, and carbohydrates. 23 Many of these compounds are vital in energy metabolism (e.g., Warburg effect) and are difficult to analyze by LC–MS because of their inherent chemical properties (e.g., chromatographic separation of isomers).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, exposure to artificial radiation has increased due to its use in cancer therapy, medical test equipment (such as X-ray-emitting computed tomography (CT) scanners), waste from the nuclear power industry, and nuclear accidents [1]. Excessive exposure to radiation causes serious health problems, because the effects include a series of molecular-, cellular-, and tissue-level processes [2].…”
Section: Introductionmentioning
confidence: 99%